Meningkatkan Kepuasan Kerja melalui Lingkungan Kerja Sosial dan Disiplin Kerja - Bintang, Argi (Journal of Business Management Education (JBME), 2020)
The issue of job satisfaction becomes an important component in the process of change of organization. So job satisfaction is still an important concern in organizations because job satisfaction affects employee productivity in achieving the goals of an organization. Problems regarding job satisfaction occur in various industries including the retail industry. The purpose of this study are to: (1) Know the description of the social work environment, (2) know the picture of work discipline, (3) know the description of job satisfaction, (4) find out the influence of the social work environment on job satisfaction, (5) know the effect of work discipline on job satisfaction.The unit of analysis in this study is employees of retail companies. The research method used in this study is quantitative. Retrieval of data by distributing questionnaires directly. The results showed that (1) social work environment in the high category, (2) work discipline in the high category, (3) job satisfaction in the high category, (4) the influence of the social work environment on job satisfaction in the category is quite strong with a contribution value of 59.13%, (5) the effect of work discipline on job satisfaction in the very strong category with a contribution value of 82.62% .Maintaining employee job satisfaction is an important thing to do because if employee job satisfaction is low it will have a negative impact on PT. A such as high absenteeism, employee work delays, turnover will have an impact on one of them on employee performance and employee morale